2012
DOI: 10.1111/j.1365-2958.2012.08199.x
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem inhibits D,D‐carboxypeptidase activity in Mycobacterium tuberculosis

Abstract: Summary Carbapenems such as meropenem are being investigated for their potential therapeutic utility against highly drug-resistant tuberculosis. These β-lactams target the transpeptidases that introduce interpeptide cross-links into bacterial peptidoglycan thereby controlling rigidity of the bacterial envelope. Treatment of M. tuberculosis (Mtb) with the β-lactamase inhibitor clavulanate together with meropenem resulted in rapid, polar, cell lysis releasing cytoplasmic contents. In Mtb it has been previously d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
162
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(175 citation statements)
references
References 50 publications
11
162
1
1
Order By: Relevance
“…This may indicate that new glycan strands (synthesized by PonA1 or PonA2) are predominantly first cross-linked in a 3-3 manner (for example, by LdtB). This model is supported by the prevalence of 3-3 crosslinks in mycobacterial PG at all growth stages (5). Our data also show that LdtB is critical for the maintenance of normal cell shape (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This may indicate that new glycan strands (synthesized by PonA1 or PonA2) are predominantly first cross-linked in a 3-3 manner (for example, by LdtB). This model is supported by the prevalence of 3-3 crosslinks in mycobacterial PG at all growth stages (5). Our data also show that LdtB is critical for the maintenance of normal cell shape (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…S7). Whereas bifunctional PBPs are critical in many bacterial species (3), mycobacterial PG exhibits very different architecture with its prevalence of 3-3 cross-links (4,5). Using allelic exchange, we found that only tiny ΔponA1 ΔldtB colonies could be seen after 21 d of growth, when ΔldtB colonies were already large ( Fig.…”
Section: Ldtb Is Critical For Normal Bacterial Fitness In Cells Withomentioning
confidence: 88%
See 2 more Smart Citations
“…Recent studies have demonstrated that the peptidoglycan layer of Mycobacterium spp. is largely cross-linked by 3¡3 transpeptide linkages (6)(7)(8). A significant effort was made to identify L,D-transpeptidases based on the hypothesis that they may be close sequence homologs of D,D-transpeptidases (9,10).…”
mentioning
confidence: 99%